Watching the Virtues : Playbills, Drama and the Teaching of Civic Virtue in the Jesuit Theatre of Poland-Lithuania - Rzegocka, Jolanta (Library of the Written Word, 2025)
In Watching the Virtues, Jolanta Rzegocka offers an account of the Jesuit theatre in the Polish-Lithuanian Commonwealth through the playbills, which record an astonishing variety of story designs and tales crafted for the stage. Her study reveals the profound role of Jesuit theatre (1564-1733) in the education of Polish-Lithuanian youth, mostly of Catholic but also of other faiths, aiming to instil virtues within the political and social fabric of the Commonwealth. Drawing from over 800 playbills, college playbooks, diaries as well as newly uncovered plays, Rzegocka paints a picture of a theatre deeply engaged with contemporary political and moral issues. She demonstrates how Jesuit theatre extended beyond educational institutions, influencing broader political discussions and public life, particularly regarding issues of authority, faith, and ethical behaviour. The study presents as a cultural phenomenon the diffusion through Jesuit theatre of Anglo-Scottish themes and narratives in Poland-Lithuania and discusses a hitherto unknown play about Thomas More (1765).